地尔硫卓上调异黏蛋白在肝癌细胞中的表达 (Nan Fang Yi Ke Da Xue Xue Bao, 2019)
OBJECTIVE: To investigate the effect of calcium channel blocker diltizem in reversing multi-drug resistance (MDR) and on metadherin expression in hepatocellular carcinoma cells and explore the molecular mechanism. METHODS: Hepatocellular carcinoma MHCC97H and 7402 cells were treated with diltiazem hydrochloride, a calcium channel blocker (0, 25, 50, 100, 200, and 400 μmol/L), for 12, 24, or 48 h. Wound healing assay was employed to assess the changes in the mobility and migration of the cells following the treatments, and the changes in the expression levels of metadherin mRNA and protein and P-gp protein were determined using RT-PCR and immunocytochemistry. RESULTS: Diltiazem hydrochloride could transiently inhibit the migration and movement of MHCC97H and 7402 cells in vitro in a time-and concentration-dependent manner (P < 0.05). Diltiazem hydrochloride at different concentrations also transiently up-regulated the expressions of metadherin mRNA and protein but did not inhibit the expression of P-gp protein in MHCC97H and 7402 cells. CONCLUSION: Calcium channel blocker can transiently inhibit the migration of hepatocellular carcinoma cells in vitro and up-regulate the expression of metadherin mRNA and protein through a feedback mechanism, suggesting the potential risk of calcium channel blockers for promoting tumor progression during the treatment of malignant tumors.